Dynamic changes in soil erosion and challenges to grain productivity in the black soil region of Northeast China - Jiawang Zhang; Ming Wang; Kai Liu; Zhan’ao Zhao (Ecological Indicators)
Soil erosion presents a significant obstacle to food and ecosystem security. This study combined multi-source data to construct a soil erosion model and challenges to grain productivity in the black soil region of Northeast China. By calculating water and wind erosion modulus between 1991 and 2020, we investigated the temporal trend, spatial aggregation, and driving and interacting factors in subregion. Soil water erosion exhibited distribution pattern of middle low and side high, with erosion average modulus was reached at 280.08 t. hm−2. a-1, and higher rates observed in summer. Precipitation and vegetation cover were combined significantly enhancement factor of 0.44. Wind erosion was concentrated in the western of Liao River Plain, the average erosion modulus is 0.81 t. hm−2. a-1. Wind erosion was relatively stable throughout the year, with two-factor enhancement factor of 0.76 attributed to soil organic matter and clay content. The expansion of cities over the last 30 years has resulted in the encroachment of 7,936 km2 of cropland. The average thickness of soil complex erosion reached 48.48 mm/a, affecting 25.23 million hectares and 1.90 million tons grain yield. Soil erosion and grain yield deterioration areas were mainly distributed in sloping cropland regions. Nearly 20,000 km2 of cropland faces the threat of soil erosion and disrupted land productivity. There is an imbalance between the land productivity and grain yield, and the proportion of severely disrupted productivity reached 27 %. Soil erosion hotspots, stabilization areas and potential hotspots in each subregion were identified, and recommendations were formulated from a subregional perspective.